Implementasi Media Daun Bunga Sepatu Untuk Mengembangkan Ketrampilan Sains Anak Usia Dini - ‘Ulya Lina, Helina Himmatul; Sulaiman, Sulaiman; Faruq, Asrul (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2025)
This research aims to investigate the application of hibiscus leaf media as a learning tool in developing science skills in early childhood. This research focuses on children aged 4-5 years, RA Hidayah Tayu's child as the research subject. The research method involves the development and implementation of a science curriculum that utilizes hibiscus leaves as a learning tool. Data was collected through participant observation, field notes, and evaluation of concept understanding. The results of this research show that the use of hibiscus leaf media can stimulate young children's interest in science skills and help develop children's initial understanding of scientific concepts. This research makes an important contribution in the context of early childhood education, by showing the potential of hibiscus leaf media as an effective learning tool for developing science skills in children's early development stages. The results of the research show that the implementation of hibiscus leaf media to develop science skills in early childhood is fun and interactive learning.